Investigation of L2/Ln Pragmatic Competence: Its Core and Route Map - Mao, Tiaoyuan (Frontiers in Psychology, 2021)
How to use language properly and acquire the capacity for language use has become the focus for linguists and philosophers for centuries. Therefore, pragmatic competence underlying language use arouses enormous interests of language acquisition practitioners. The article reveals core properties of various models or theories of pragmatic competence, such as communicative componential models, functionalist’s form-function mapping proposal, tripartite cognitive model and the current Integrated Model of Pragmatic Competence. The common core includes (but not limited to) integration of thought and communication, one uniform pragmatic mechanism, dynamic form-function mapping and complementarity between grammatical and pragmatic competences. With the findings as a departure, a brief outline for further investigation of pragmatic competence is proposed finally, including pathological and neurobiological examination of pragmatic competence.